Distribution of Maps with Transversal Homoclinic Orbits in a Continuous Map Space - Qiuju Xing; Yuming Shi (Abstract and Applied Analysis)
This paper is concerned with distribution of maps with transversal homoclinic orbits in a continuous map space, which consists of continuous maps defined in a closed and bounded set of a Banach space. By the transversal homoclinic theorem, it is shown that the map space contains a dense set of maps that have transversal homoclinic orbits and are chaotic in the sense of both Li-Yorke and Devaney with positive topological entropy.